Integrasi Digital Marketing dan Community-Based Tourism dalam Pengembangan Agrowisata di Desa Warjabakti Kabupaten Bandung - Susanti, Hesty; Rahmawati, Dien; Mukhtar, Husneni; Wibowo, Suryo Adhi; Priharti, Wahmisari; Cahyadi, Willy Anugrah; Nugroho, Bambang Setia; Aziz, Burhanuddin; Susanto, Kusnahadi (Universitas AMIKOM Yogyakarta, 2024)
Warjabakti Village has various agro-tourism potentials that have not been managed properly, namely in the form of a charming natural scenery, natural conditions that are still maintained, and cool air. The problems faced are the need for more exposure to technology, the unavailability of supporting facilities and infrastructure, and the absence of groups capable of coordinating these potentials. This community service aims to develop a community-based tourism system by integrating digital marketing technology to empower target communities. The results achieved from this community service activity are the formation of Pokdarwis, which have been legally approved by the village government and will oversee the management of the tourism village in Warjabakti Village with governance that the team and partners have made. In addition, the e-digital map and the Haruman Tourism Village website have been produced. This website contains village content and branding that displays attractive village information, videos, and animations that have been structured and integrated, as well as a complete and attractive e-digital map of tourist areas.